Identity, Displacement and Obscuring the Native Personality: Towards Decolonising Indigenous Folks in Ìlàjẹ Names - Segun Omosule; Stephen Ajimisan (Yoruba Studies Review)
Fulfilment takes diverse forms and superimposing identity on supposed subjects who attempt to imitate whatever belongs to the impostor and considering it as the best standard they could imitate is the greatest form of satisfaction that a group of people that are not remotely connected could have from an overseas people. Apart from subsuming the identity of the people in the overall supremacy of the tiny people of an island in Britain, colonialism represents a subtle robbery of the possessions of the weak. Twenty indigenous surnames in the Ìlàjẹ/Ìkálẹ̀ communities of Ondo State exemplify the immediate and long-term goals of the colonialists. The names are interpreted and divorced of their underlying colonial undertones which seek to praise and arrogate positive vibrations to the subsisting relationship between the folks and those who colonized them. While deploying the tool of post-colonialism, the essay unravels the tool of diplomacy, exaggeration and arrogation of divine capabilities to themselves as reasons for the holistic acceptance of the colonialists as next to God, superhuman and greater than the black folks.